Circe : a novel - Miller, Madeline (Little, Brown and Company, 2018)
Follows Circe, the banished witch daughter of Helios, as she hones her powers and interacts with famous mythological beings before a conflict with one of the most vengeful Olympians forces her to choose between the worlds of the gods and mortals.